Norges Bank's Financial Sector Role in the Period 1945-2013, with a Particular Focus on Financial Stability - Harald Haare; Arild J. Lund; Jon A. Solheim (Norges Bank, 2016)
This article is a slightly revised version of Chapter II (the summary) of Norges Bank's Occasional Paper No. 48, published in Norwegian, which surveys financial sector developments and Norges Bank's financial sector role in the period 1945-2013. In particular, it documents the main developments and the central bank's handling of the Norwegian banking crisis in 1987-1993 and the global financial crisis in 2007-2009. The Occasional Paper forms part of Norges Bank's Bicentenary Project marking the Bank's 200th anniversary in 2016.
hdl:11250/2506540
Keywords: 330